Comparative Transcriptome Analysis of Onion in Response to Infection by Alternaria porri (Ellis) Cifferi - Khandagale, Kiran; Roylawar, Praveen; Kulkarni, Onkar; Khambalkar, Pravin; Ade, Avinash; Kulkarni, Abhijeet; Singh, Major; Gawande, Suresh (Frontiers in Plant Science, 2022)
Purple blotch (PB) is one of the most destructive foliar diseases of onion and other alliums, caused by a necrotrophic fungal pathogen Alternaria porri. There are no reports on the molecular response of onion to purple blotch infection. To elucidate the response of onion to A. porri infection, we consequently carried out an RNAseq analysis of the resistant (Arka Kalyan; AK) and susceptible (Agrifound rose; AFR) genotype after an artificial infection. Through differential expression analyses between control and pathogen-treated plants, we identified 8064 upregulated and 248 downregulated genes in AFR, while 832 upregulated and 564 downregulated genes were identified in AK. A further significant reprogramming in the gene expression profile was also demonstrated by a functional annotation analysis. GO terms, which are particularly involved in defense responses and signaling, are overrepresented in current analyses such as ‘oxidoreductase activity’, ‘chitin catabolic processes, ‘defense response’ etc. Several key plant defense genes were differentially expressed upon A. porri infection which includes PR proteins, receptor-like kinases, phytohormones signaling, cell-wall integrity, cytochrome P450 monooxygenases, transcription factors etc. Some of the genes were exclusively overexpressed in resistant genotype; GABA transporter1, ankyrin repeat domain-containing protein, xyloglucan endotransglucosylase/hydrolase, PR-5 (Thaumatin-like) etc. Antioxidant enzyme activities were observed to be increased after infection in both genotypes but higher activity was found in the resistant genotype, AK. This is the first report of transcriptome profiling in onion in response to PB infection and will serve as a resource for future studies to elucidate the molecular mechanism of onion-A. porri interaction and to improve PB resistance in onions.